2009
DOI: 10.4049/jimmunol.0901465
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of TLR2 Does not Reverse the Suppressor Function of Mouse Regulatory T Cells, but Promotes Their Survival

Abstract: TLRs are a class of conserved pattern recognition receptors that are used by cells of the innate immune system. Recent studies have demonstrated the expression of TLRs on both human and mouse T cells raising the possibility that TLRs play a direct role in adaptive immunity. TLR2 is activated primarily by bacterial wall components including peptidoglycan and lipoproteins. Several studies have shown that mouse regulatory T (Treg) cells express TLR2 and claimed that engagement of TLR2 by synthetic ligands reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 34 publications
8
100
6
Order By: Relevance
“…The inability of Tregs to produce IL-2, IFN-g, RANTES, and IP-10 is caused by the constitutive expression of FoxP3, which can bind to the forkhead-binding sites located within promoter regions of cytokine genes and thus suppress cytokine production and probably chemokine production (40). In accordance with data in the mouse model (30), we observed that the treatment of human Tregs with TLR2 ligands did not downregulate FoxP3 protein expression. In contrast to the murine counterpart (28-30), TLR2 treatment and TCR activation of human Tregs induced a further upregulation of intracellular FoxP3, explaining the sustained suppression of cytokine production in human Tregs after activation.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The inability of Tregs to produce IL-2, IFN-g, RANTES, and IP-10 is caused by the constitutive expression of FoxP3, which can bind to the forkhead-binding sites located within promoter regions of cytokine genes and thus suppress cytokine production and probably chemokine production (40). In accordance with data in the mouse model (30), we observed that the treatment of human Tregs with TLR2 ligands did not downregulate FoxP3 protein expression. In contrast to the murine counterpart (28-30), TLR2 treatment and TCR activation of human Tregs induced a further upregulation of intracellular FoxP3, explaining the sustained suppression of cytokine production in human Tregs after activation.…”
Section: Discussionsupporting
confidence: 79%
“…These data are in contrast to the murine counterpart in which TLR2 ligand treatment of Tregs is linked to a concomitant proliferative activity of these cells in the absence of IL-2 (28). Others, however, have reported that the addition of exogenous IL-2 is necessary for proliferation of murine Tregs upon TCR/TLR2 ligand stimulation in vitro (29,30). In contrast to the experiments with murine Tregs by Chen et al (30), we observed that pretreatment of human Tregs with TLR2 ligands resulted in an abrogation of their suppressive activity on cytokine production by responder T cells.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations